Allergic‐like reactions to asparaginase: Atypical allergies without asparaginase inactivation. Issue 11 (4th July 2016) - Kloos, Robin Q. H.; Pieters, Rob; Escherich, Gabriele; van der Sluis, Inge M.
Abstract: Background: Asparaginase is an important component of pediatric acute lymphoblastic leukemia (ALL) therapy. Unfortunately, this treatment is hampered by hypersensitivity reactions. In general, allergies – regardless of severity – cause complete inactivation of the drug. However, we report atypical allergic reactions without inactivation of asparaginase, here called allergic‐like reactions. Procedure: Patients with an allergic‐like reaction, who were treated according to the Dutch Childhood Oncology Group ALL‐11 or the CoALL 08–09 protocol, were described. The reactions were identified by continual measurement of asparaginase activity levels. Characteristics, including timing of occurrence, symptoms, grade, and the presence of antiasparaginase antibodies, were compared to those of real allergies. Results: Fourteen allergic‐like reactions occurred in nine patients. Five reactions were to PEGasparaginase and nine to Erwinia asparaginase. Allergic‐like reactions occurred relatively late after the start of infusion compared to real allergies. Antibodies were absent in all but one patient with an allergic‐like reaction, while they were detected in all patients with a real allergy. Symptoms and grade did not differ between the groups. Asparaginase was continued with the same formulation in six patients of whom four finished treatment with adequate activity levels. Conclusions: In conclusion, allergic‐like reactions occur relatively late after the start of infusion and without antibodies. Despite these clinical differences, allergic‐like reactions can only be distinguished from real allergies by continually measuring asparaginase activity levels. If clinically tolerated, formulations should not be switched in case of allergic‐like reactions. Moreover, failure to recognize these reactions may lead to a less favorable prognosis if asparaginase therapy is terminated unnecessarily.